Enhancing Resistant Starch and Functional Properties of Corn Flour via Dual Modification with Organic Acids and Annealing - Akhmad Mustofa; Vivi Nuraini; Eri Wahyu Riadi; Kelvin Matthew Richardo; Dinda Fitria (Journal of Applied Agricultural Science and Technology, 2026)
Corn flour holds a potential for functional food through chemical and thermal modification. This study examines the impact of dual modification—organic acid esterification (using citric, acetic, or lactic acid) followed by annealing—on the physicochemical and morphological properties of corn flour. Citric acid treatment, combined with annealing, yielded the lowest swelling power and the highest clarity, indicating improved stability and transparency. Acetic acid modification produced the highest RS values, suggesting strong applicability in functional food development. The increase in RS content implies potential health benefits such as glycemic control and gut microbiota modulation, making the modified flour suitable for preventive nutrition applications